CORROSION RESISTANCE OF DYNAMIC LOADED CAST ALLOY AS12 - A. A. Andrushevich; S. M. Usherenko (Литьë и металлургия)
The assessment of influence of powder particles in the mode of super deep penetration (SDP) on change of corrosion resistance of aluminum cast alloy AK12 is executed. The aluminum alloy reinforced by fiber zones with the reconstructed structure has the increased corrosion resistance.